Defluorinative functionalization approach led by difluoromethyl anion chemistry - Kensuke Muta; Kazuhiro Okamoto; Hiroki Nakayama; Shuto Wada; Aiichiro Nagaki (Nature Communications)
Abstract Organofluorine compounds have greatly benefited the pharmaceutical, agrochemical, and materials sectors. However, they are plagued by concerns associated with Per- and Polyfluoroalkyl Substances. Additionally, the widespread use of the trifluoromethyl group is facing imminent regulatory scrutiny. Defluorinative functionalization, which converts the trifluoromethyl to the difluoromethyl motifs, represents the most efficient synthetic strategy. However, general methods for robust C(sp 3 )–F bond transformations remain elusive due to challenges in selectivity and functional group tolerance. Here, we present a method for C(sp 3 )–F bond defluorinative functionalization of the trifluoromethyl group via difluoromethyl anion in flow. This new approach tames the reactive difluoromethyl anion, enabling diverse functional group transformations. Our methodology offers a versatile platform for drug and agrochemical discovery, overcoming the limitations associated with fluorinated motifs.